The applicability of remedial secession on Iraqi Kurdistan under international law: analysis with reference to the Kosovo's case - Ahmed, Redar Bakr (2021)
This is an exploratory and legal analytical study on the application of the principle of remedial secession to the issue of the Kurdistan Region of Iraq in international law and includes an analysis of the Kosovo case and other similar cases. The application of the principle of remedial secession is also attempted as a possible solution for regions with similar problems regarding separation or independence. This study engages in the analysis and investigation of the most important legal factors behind the Kurdistan Region’s struggle for a separation from Iraq through the principle of remedial secession although there are other legal factors that encouraged the Kurdistan Region to achieve the legality for a secession request from Iraq. Adopting qualitative methodology, 20 distinguished and entrusted decision-makers in the Kurdistan Regional Government (KRG) of Iraq were interviewed in this study using semi-structured and face-to-face approaches. Out of the 20, nine of them are at present partisan leaders and decision makers of the KRG while seven of them are from the academia and specialists in international law. Four interviewees are experienced and prominent people in the Kurdish National Liberation Movement who personally witnessed the events and conflicts of the Kurdistan Region. The interview data was analysed through an analytical, manual, and regular process. This study finds that there are sufficient legal factors for the Kurdistan Region to demand for separation to solve its problems with Iraq. Thus, the solution recommended by this study for the issues of the Kurdistan Region and its issues with Iraq is through the the application of the principle of remedial secession as the Kurdistan Region has the necessary conditions and sufficient factors to do so. In addition, taking Ko sovo’s previous experience and negotiations with Serbia as a benchmark, it would show that the issues between Kurdistan Region and Iraqi government have not been solved. Thus, this study could serve as a guide for a solution of the Kurdistan Region issues with Iraq through the principle of remedial secession.